A new interpretation of Madagascar's megafaunal decline: The "Subsistence Shift Hypothesis". Issue 130 (May 2019) - Godfrey, Laurie R.; Scroxton, Nick; Crowley, Brooke E.; Burns, Stephen J.; Sutherland, Michael R.; Pérez, Ventura R.; Faina, Peterson; McGee, David; Ranivoharimanana, Lovasoa
Abstract: Fundamental disagreements remain regarding the relative importance of climate change and human activities as triggers for Madagascar's Holocene megafaunal extinction. We use stable isotope data from stalagmites from northwest Madagascar coupled with radiocarbon and butchery records from subfossil bones across the island to investigate relationships between megafaunal decline, climate change, and habitat modification. Archaeological and genetic evidence support human presence by 2000 years Before Common Era (BCE). Megafaunal decline was at first slow; it hastened at ∼700 Common Era (CE) and peaked between 750 and 850 CE, just before a dramatic vegetation transformation in the northwest that resulted in the replacement of C3 woodland habitat with C4 grasslands, during a period of heightened monsoonal activity. Cut and chop marks on subfossil lemur bones reveal a shift in primary hunting targets from larger, now-extinct species prior to ∼900 CE, to smaller, still-extant species afterwards. By 1050 CE, megafaunal populations had essentially collapsed. Neither the rapid megafaunal decline beginning ∼700 CE, nor the dramatic vegetation transformation in the northwest beginning ∼890 CE, was influenced by aridification. However, both roughly coincide with a major transition in human subsistence on the island from hunting/foraging to herding/farming. We offer a new hypothesis, which we call the "Subsistence Shift Hypothesis, " to explain megafaunal decline and extinction in Madagascar. This hypothesis acknowledges the importance of wild-animal hunting by early hunter/foragers, but more critically highlights negative impacts of the shift from hunting/foraging to herding/farming, settlement by new immigrant groups, and the concomitant expansion of the island's human population. The interval between 700 and 900 CE, when the pace of megafaunal decline quickened and peaked, coincided with this economic transition. While early megafaunal decline through hunting may have helped to trigger the transition, there is strong evidence that the economic shift itself hastened the crash of megafaunal populations.